E0040 The expression of signal transduction pathway of TGF1Smad in the rat cardiac tissue with type 2 diabetes and intervention by atorvastatin. (17th November 2010) - Xiaohong, Yang; Wei, Cui; Bangrong, Zhao; Jingchao, Lu; Fan, Liu; Jun, Du
Abstract : Objective: Observation on changes of signal transduction pathway of TGF-β1 /Smad in the course of myocardial fibrosis in the rat with type 2 diabetes and preventive effect of atorvastatin. Methods: The experimental type 2 diabetic rats were yielded by injecting streptozotocin (STZ, 30 mg/kg) and fed with high fat and glucose food, then intervention by atorvastatin (20 mg·kg −1 ·d −1 ) for 12 weeks. Collagen content was observed by Masson staining. RT-PCR was used to observe the gene expression of TGF-β1 in experiment rat hearts. The protein expression and tissue localisation of TGF-β1, Smad2/3, Smad7 and were observed with the immunohistochemistry. Results: The interstitial collagen accumulation and thickened capillary basement membrane in the atorvastatin (Masson stain: 0.80±0.16) administration group was obviously relieved compared with that of the DM (1.36±0.16)group (p<0.01). The expression levels of TGF-β1 mRNA in the DM group was obviously increased compared with that of the control group (1.39±0.10 vs 0.16±0.02, p<0.01). The expression levels of TGF-β1 mRNA in the atorvastatin administration groups was obviously reduced compared with that of the DM group (0.57±0.04 vs 1.39±0.10, p<0.01). Immunohistochemistry: the positive expressions of Smad2/3 and TGF-β1 were present in fibroblasts, vascular endothelial and myocardial cells in the control group. The positive expressions of Smad2/3 (10.02±2.32 vs 1.12±0.11, p<0.01) and TGF-β1 (18.19±1.39 vs 3.93±0.46, p<0.01) were even darker and larger in size compared with that in the control group in view of their optic density. There were only the vascular endothelial cells and a few of fibroblasts in the atorvastatin groups were the Smad2/3 (10.0±2.32 vs 5.16±0.17, p<0.01) and TGF-β1 (18.19±1.39 vs 10.21±1.08, p<0.01) positive, but shallow in colour, the positive optic density was reduced obviously compared with that of DM group. In DM group the positive cells of Smad7 mainly distributed in the vascular endothelial cells, fibroblasts, myocardial cells, the numbers of the positive cells was reduced compared with that of the control group (1.26±0.31 vs 10.16±0.64, p<0.01). In atorvastatin group the positive cells of Smad7 was increased in such cells as those mentioned above, especially in the vascular endothelial cells (1.26±0.31 vs 4.00±0.20, p<0.01). Conclusion: By way of inhibition activations of pathway of TGF-β1 /Smad, atorvastatin may obviously relieve the collagen accumulation and fibrosis in myocardium, thus delay the progress of the diabetic cardiomyopathy.